Four new crane fly species of the subgenus Vestiplex (Diptera: Tipulidae: Tipula) from Tibet and Yunnan, China - Men, Qiulei; Sun, Zhongqiu; Starkevich, Pavel (European Journal of Taxonomy, 2023)
Four new crane fly species of the subgenus Tipula (Vestiplex) Bezzi, 1924, T. (V.) medialobata sp. nov. (Yunnan), T. (V.) singularis sp. nov. (Yunnan), T. (V.) cibagouensis sp. nov. (Tibet) and T. (V.) paramonovi sp. nov. (Tibet) are described and illustrated. Redescription and detailed illustrations of T. (V.) nestor Alexander, 1934 are provided with first distributional record in mainland China.